Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides

Surface texture and specific adsorption sites of sol-gel synthesized anatase TiO2 nanoparticles - Zaki, Mohamed I.; Mekhemer, Gamal A. H.; Fouad, Nasr E.; Jagadale, Tushar C.; Ogale, Satishchandra B. (Materials Research Bulletin, 2010)
The surface properties of sot-gel synthesized anatase titania (TiO2) nanoparticles are probed by sorptiometry, infrared absorption spectroscopy, UV-vis diffuse reflectance spectroscopy and high resolution transmission electron microscopy. The results reveal strong correlations of the surface area, porosity, pyridine adsorption capacity and strength, and catalytic methylbutynol decomposition activity. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Oxides; Sol-gel chemistry; X-ray diffraction